Efficacy of omalizumab in reducing latex allergy - Aruanno, Arianna; Chini, Raffaella; Nucera, Eleonora (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Omalizumab, a humanized monoclonal antibody that binds the CH3 domain near the binding site for the high affinity type-I IgE Fc receptors of human IgE, can neutralize free IgE and inhibit the IgE allergic pathway [1]. The current indications for treatment with omalizumab are limited to severe persistent allergic asthma and chronic spontaneous urticaria (CSU) when it is not controlled by conventional anti-H1 treatment at the maximum dosage. In recent years, several studies [1] have shown that omalizumab is effective in a large number of IgE-mediated and non-IgE-mediated disorders, indicating that omalizumab treatment acts on many levels and not only on immunoglobulins E [2].